Influence of working pressure and lasing energy of Al plasma in laser-induced breakdown spectroscopy - Abbas, Qusay Adnan (Iraqi Journal of Physics, 2019)
Aluminum plasma was generated by the irradiation of the targetwith Nd: YAG laser operated at a wavelength of 1064 nm. Theeffect of laser power density and the working pressure on spectrallines generating by laser ablation, were detected by using opticalspectroscopy. The electron density was measured using the Starkbroadening of aluminum lines and the electron temperature byBoltzmann plot method it is one of the methods that are used. Theelectron temperature Te, electron density ne, plasma frequencyand Debye length increased with increasing the laser peakpower. The electron temperature decrease with increasing gaspressure.